PENGARUH KUALITAS PELAYANAN DAN KUALITAS INFORMASI TERHADAP KEPUASAN PELANGGAN PADA PT. PLN (PERSERO) UP3 TOBELO - Gedoa, Paulus; Hi. Posi, Sahrul (Servqual: Jurnal Ilmu Manajemen, 2023)
This research aims to determine the quality of service and quality of information on customer satisfaction at PT. PLN (Persero) UP3 Tobelo. This type of research is quantitative. The total research population was 68,372. The sample was determined using the Sloving formula as many as 100 people. The analysis method used is the Multiple Linear Regression method. The research results show that the service quality variable (X1) has a partially significant positive effect on customer satisfaction. The information quality variable (X2) has a partially significant positive effect on customer satisfaction. Simultaneous tests show that the service quality variables (X1) and customer satisfaction X2) together have a significant effect on customer satisfaction. Furthermore, from the determinant coefficient test (R2), the R-square value was only 0.301 or 30.1%. This shows that 30.1% of customer satisfaction is influenced by service quality and information quality variables while the remaining 69.9% (100% - 69.9%) is influenced by other factors not explained in this research, therefore it is hoped that further research to add other variables.